The budget purposes on the influence of institutional isomorphism on self-rejection - Pereira da Luz, Igor (2020)
The study aimed to examine the influence of institutional isomorphism on self-rejection to the budget, mediated by the artifact's purposes. It is important to study the Brazilian pharmaceutical sector, as it represents a peculiar example of institutional discussion, considering the pressures of institutional isomorphism suffered by the sector. The study is descriptive, with a quantitative approach, characterized as survey research. to achieve the research objective, the assumptions of DiMaggio and Powell (1983), the strategic responses to challenge and manipulate Oliver's conceptual model (1991) and the budget purposes used by Ekholm and Wallin (2011) were used. The selected population was the managers of companies in the pharmaceutical sector linked to the Guia da Farmácia, and the final sample consisted of 147 valid responses. For data analysis, the Structural Equation Modeling was used. The study results show a positive influence of institutional isomorphism in the purposes of planning and dialogue. However, the influence of the budget's purposes on self-rejection was not found. Institutional isomorphism still had a positive influence on budget self-rejection. As contributions, the study brings evidence that the factors of isomorphism lead to a better use of the purposes of the budget, also lead to a rejection of the artifact, which may be linked to factors of multiplicity and restriction.